STRATEGI KANTOR IMIGRASI KELAS I TPI DENPASAR DALAM MEMPERTAHANKAN PREDIKAT WILAYAH BEBAS KORUPSI (WBK) DAN WILAYAH BIROKRASI BERSIH MELAYANI (WBBM) - Ni Putu Ayu Yudanti; I Putu Dharmanu Yudartha; Juwita Pratiwi Lukman (Triwikrama: Jurnal Ilmu Sosial, 2025)
The WBK and WBBM predicates are given to a work unit that has passed the standardization. This research aims to determine the strategy of the Denpasar Immigration Office in maintaining the title of Corruption Free Area (WBK) and Clean Serving Bureaucratic Area (WBBM). The research method is qualitative descriptive and data collection methods in the form of interviews, observation and documentation. The research results show that the implemented strategy has been able to maintain the WBK and WBBM predicate but still needs to be optimized. There are problems in the form of technology, infrastructure and human resource management. The strategic recommendations from SWOT Analysis: (1) reinforce the consistency of procedures to maintain IKM (SO), (2) increasing maintenance of digitalization systems by a collaboration with private sector (WO), (3) reinforce work system procedures to avoid corruption (ST), and (4) optimizing digital systems with high security (WT). This research recommends strengthening procedures, improving facilities and optimizing digital-based systems.